DATA LUAS HUTAN PERKECAMATAN DI KABUPATEN BLORA - Arivian Mujahid (ADMIN: Jurnal Administrasi Negara, 2024)
Blora Regency is one of the districts in Central Java Province with an area of 1,820.59 km². Forests are one of the important natural resources for Blora Regency. Forests function as a life support, oxygen provider, and source of livelihood for the community. This research aims to determine data on the area of sub-district forests in Blora Regency. The data used in this research is secondary data from the Blora Regency Central Statistics Agency. This data includes data on the area of sub-district forests in 2023. The research results show that the forest area in Blora Regency in 2023 will be 90,416.52 hectares. The forest area is spread across 18 sub-districts in Blora Regency. The distribution of forest area in Blora Regency is uneven. The district with the largest forest area is Randublatung District, which is 13,711.82 hectares. Meanwhile, the sub-district with the smallest forest area is Ngawen Sub-district, which is 1,069.74 hectares